The complete chloroplast genome of Cenchrus ciliaris (Poaceae) - Pritesh P. Bhatt; Vrinda S. Thaker (Mitochondrial DNA. Part B. Resources, 2018)
Cenchrus ciliaris is an important pasture resource for arid region and owing to apomixis, it has been very important for development and distribution of cultivars and agro-types. In present study complete chloroplast genome of C. ciliaris was sequenced. The size of chloroplast genome is 138737 bp length with overall GC content 38.6%. It exhibited regular quadripartite structure with 81053 bp of LSC region, 16108 bp of SSC region and 20788 bp of each IR region. A total of 130 genes were identified, including 87 coding genes, 32 tRNAs, 7 ribosomal RNAs and 4 pseudogenes. Phylogenetic analysis was performed using 13 other members representing major subfamilies of Poaceae.